2016
DOI: 10.3390/molecules21101281
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Samarium Doped Fluorapatites and Their Catalytic Activity towards Synthesis of 1,2,4-Triazoles

Abstract: An investigation was conducted into the influence of the amino acids as organic modifiers in the facile synthesis of metal incorporated fluorapatites (FAp) and their properties. The nanostructured Sm doped fluorapatites (Sm-FAp) were prepared by a co-precipitation method using four different amino acids, namely glutamic acid, aspartic acid, glycine and histidine. The materials were characterized by various techniques including X-ray diffraction (XRD), Fourier transform infra-red spectroscopy (FT-IR), field emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…FAp also provided a satisfactory yield of the desired product (Table 1, Entry 19). FAp exhibits an amphoteric feature having both Lewis acid and basic sites, with the Ca 2+ accountable for the acidic sites, and F − and P–O − being liable for the basic sites . This combination allows effective conversions, which explains the superior catalytic performance of FA.…”
Section: Resultsmentioning
confidence: 99%
“…FAp also provided a satisfactory yield of the desired product (Table 1, Entry 19). FAp exhibits an amphoteric feature having both Lewis acid and basic sites, with the Ca 2+ accountable for the acidic sites, and F − and P–O − being liable for the basic sites . This combination allows effective conversions, which explains the superior catalytic performance of FA.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclocondensation of thiosemicarbazide with aldehydes could afford either 1,2,4-triazolidine-3-thiones or 2-amino-1,3,4-thiadiazoline using different reaction conditions (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). We observed that there is a structural elucidation confusion between the open structure of thiosemicarbazone and their cycloaddition product with aldehyde.…”
Section: Introductionmentioning
confidence: 88%
“…That was obvious in several published articles which reported identical spectral data for both thiosemicarbazones and their cycloaddition product (1,2,4-triazolidine-3-thiones). Thus, many authors incorrectly interpreted the NMR spectral data of alkylidene thiosemicarbazones and reported them as triazolidine-3-thiones (45)(46)(47)(48)54,55,57), this confusion arises from the presence of three exchangeable N-H signals in both structures. Herein, we would like to report a green and simple method for synthesis of alkylidene thiosemicarbazide and clarify the structural elucidation confusion between alkylidene thiosemicarbazide, and their cyclized forms.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our research efforts in the direction of synthesis of various heterocyclic molecules via MCRs under green conditions, recently we have reported the preparation of several novel heterocyclic protocols via multicomponent reaction in the presence of different heterogeneous catalysts . Further, we have also reported biological active heterocyclic molecules .…”
Section: Introductionmentioning
confidence: 92%